Sujeitos da educação de jovens e adultos da UFMG e o acesso à informação no mundo digital e na prática cotidiana: desafios - Eliane Apolinário Vieira Avelar (2020)
This thesis reports on a study aimed at understanding and analyzing the difficulties and limitations faced by youth and adult education (YAE) students when using information and communication technologies (ICTs) in everyday activities. The research also aimed at analyzing how YAE helped those students handle ICTs as a step toward becoming autonomous citizens. The sample consisted of 15 senior middle-school students (9 females and 6 males) from project “Ensino Fundamental de Jovens e Adultos 2º Segmento (PROEF 2)”, carried out by Centro Pedagógico (CP), a school of basic and professional education at Universidade Federal de Minas Gerais (UFMG). Data collection consisted of document research and semi-structured interviews, which were content analyzed. This qualitative method showed that most students had had some level of school experiences in their childhood, but they had to drop school for several reasons, including: work to support their families, and engagement in romantic relationships. The latter reason was especially important for the females. In contrast, different reasons explained their return to school, such as labor market requirements, family incentives, university environment, and expectations of graduating. Data also showed that smartphones play a central role in ensuring YAE students’ daily access to the Internet. Particularly, voice command is a useful functionality in their daily activities and access to public services is a common reason for them to use ICTs. Nevertheless, the participants depended on young people to help them on several occasions. Despite the students’ awareness, the YAE course in question focused very little on the use of ICTs. This thesis contributes in different ways to the body of knowledge on YAE and ICT: 1) it focuses on students’ daily activities outside the school, 2) it shows that the university environment (in opposition to traditional schools environment) was important for the students, 3) it provides evidence of the role of ICTs for social inclusion of YAE students, especially considering that mastering these technologies could be understand as a new form of power in our society, and 4) it emphasizes the importance of ICT to support the individual’s autonomy in the digital era. It concludes that a way to refine this essential aspect is including the teaching of ICTs in the YAE classrooms.